Microcephaly and Zika virus: a clinical and epidemiological analysis of the current outbreak in Brazil, - Magda Lahorgue Nunes; Celia Regina Carlini; Daniel Marinowic; Felipe Kalil Neto; Humberto Holmer Fiori; Marcelo Comerlato Scotta; Pedro Luis Ávila Zanella; Ricardo Bernardi Soder; Jaderson Costa da Costa (Elsevier, 2016)
Abstract Objective: This study aimed to critically review the literature available regarding the Zika virus outbreak in Brazil and its possible association with microcephaly cases. Sources: Experts from Instituto do Cérebro do Rio Grande do Sul performed a critical (nonsystematic) literature review regarding different aspects of the Zika virus outbreak in Brazil, such as transmission, epidemiology, diagnostic criteria, and its possible association with the increase of microcephaly reports. The PubMed search using the key word "Zika virus" in February 2016 yielded 151 articles. The manuscripts were reviewed, as well as all publications/guidelines from the Brazilian Ministry of Health, World Health Organization and Centers for Disease Control and Prevention (CDC - United States). Summary of findings: Epidemiological data suggest a temporal association between the increased number of microcephaly notifications in Brazil and outbreak of Zika virus, primarily in the Brazil's Northeast. It has been previously documented that many different viruses might cause congenital acquired microcephaly. Still there is no consensus on the best curve to measure cephalic circumference, specifically in preterm neonates. Conflicting opinions regarding the diagnosis of microcephaly (below 2 or 3 standard deviations) that should be used for the notifications were also found in the literature. Conclusion: The development of diagnostic techniques that confirm a cause-effect association and studies regarding the physiopathology of the central nervous system impairment should be prioritized. It is also necessary to strictly define the criteria for the diagnosis of microcephaly to identify cases that should undergo an etiological investigation.